Analisis Sengketa Batas Wilayah dan Urgensi Integrasi Kebijakan Konstitusional untuk Stabilitas Daerah - Wegel Rafael Angelo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Regional boundary disputes have a significant impact on government functions and development at the provincial or district level. One of the main impacts is duplication of administration between two conflicting government entities, which can lead to waste of resources and confusion regarding administrative responsibilities. Apart from that, legal and policy uncertainty can also arise due to lack of clarity regarding territorial boundaries, disrupting the implementation of government regulations and policies. Delays in the implementation of public services such as education, health and infrastructure also often occur due to these disputes, hampering development in the disputed areas. Disruption to leadership and political stability can also occur, because territorial boundary disputes affect elections and leadership duties in the disputed region, creating political uncertainty and hampering the decision-making process. This research uses literature study methods and analysis of documents or data taken from several journals or searching on the internet, where the data is collected and used as a discussion in this paper.